2009
DOI: 10.1111/j.1582-4934.2009.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivin is an essential mediator of arthritis interacting with urokinase signalling

Abstract: Proto-oncogene survivin has recently been identified as a prognostic marker distinguishing patients with destructive rheumatoid arthritis (RA). In the present material of 132 RA patients and 82 controls, the levels of survivin correlated to urokinase (uPA) (r= 0.46), a plasminogen activator over-expressed in inflamed joints and known to exhibit potent arthritogenic properties. Here we evaluate the functional relationship between these proteins using primary synovial fibroblasts and leucocytes of RA patients, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 45 publications
(59 reference statements)
0
28
1
Order By: Relevance
“…High levels of survivin were also detected in the rheumatoid synovia where the expression of survivin correlated with the synovial infiltration with macrophages and memory T cells and with the low rate of apoptosis. These findings suggested a key function for survivin in the regulation of invasive properties of fibroblasts in the inflamed rheumatic joint [24-26]. The result of our study is not consistent with these findings, since the concentration of survivin was increased before the patients presented any symptoms of joint disease.…”
Section: Discussioncontrasting
confidence: 82%
“…High levels of survivin were also detected in the rheumatoid synovia where the expression of survivin correlated with the synovial infiltration with macrophages and memory T cells and with the low rate of apoptosis. These findings suggested a key function for survivin in the regulation of invasive properties of fibroblasts in the inflamed rheumatic joint [24-26]. The result of our study is not consistent with these findings, since the concentration of survivin was increased before the patients presented any symptoms of joint disease.…”
Section: Discussioncontrasting
confidence: 82%
“…Considering that increased cell proliferation and resistance to apoptosis contribute to increased numbers of FLS and chronic inflammatory cells in rheumatoid joints [18], survivin has important implications for the pathogenesis of RA. It has been reported that survivin may be an essential invasive mediator in RA through urokinase [19]. Survivin and xIAP are expressed in active rheumatoid synovium, suggesting the inhibition of apoptosis in RA cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…uPAR is expressed in multiple cells, such as monocytes, macrophages, T cells [18,19]. The uPAR expression is elevated during inflammation and tissue remodeling, and is associated with the development of inflammatory diseases, such as RA, periodontitis, cancer, and fibrosis [19][20][21][22][23][24][25]. uPAR also plays an important role in the regulation of bone homeostasis by influencing OB function and OC formation under non-inflammatory condition [26,27].…”
Section: Introductionmentioning
confidence: 99%